Paschima Odishara Paramparik Krida : Ek Loakatatwika Adhyayana - Sanjaya Kumar Bag (Trupti, Gouri Nagar, Bhubaneswar, 2012)
The book is about folk culture in Odisha
Keywords: Odia; Paschima Odishara Paramparik Krida : Ek Loakatatwika Adhyayana; Folk Culture; Odia; Odia